The role of the peripheral system dysfunction in the pathogenesis of sepsis-associated encephalopathy - Zhang, Jingyu; Chen, Shuangli; Hu, Xiyou; Huang, Lihong; Loh, PeiYong; Yuan, Xinru; Liu, Zhen; Lian, Jinyu; Geng, Lianqi; Chen, Zelin; Guo, Yi; Chen, Bo (Frontiers in Microbiology, 2024)
Sepsis is a condition that greatly impacts the brain, leading to neurological dysfunction and heightened mortality rates, making it one of the primary organs affected. Injury to the central nervous system can be attributed to dysfunction of various organs throughout the entire body and imbalances within the peripheral immune system. Furthermore, central nervous system injury can create a vicious circle with infection-induced peripheral immune disorders. We collate the pathogenesis of septic encephalopathy, which involves microglial activation, programmed cell death, mitochondrial dysfunction, endoplasmic reticulum stress, neurotransmitter imbalance, and blood-brain barrier disruption. We also spotlight the effects of intestinal flora and its metabolites, enterocyte-derived exosomes, cholinergic antiinflammatory pathway, peripheral T cells and their cytokines on septic encephalopathy.